1996
DOI: 10.1002/j.1460-2075.1996.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective interaction of JNK protein kinase isoforms with transcription factors.

Abstract: The JNK protein kinase is a member of the MAP kinase group that is activated in response to dual phosphorylation on threonine and tyrosine. Ten

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
1,077
4
6

Year Published

1997
1997
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,249 publications
(1,118 citation statements)
references
References 53 publications
31
1,077
4
6
Order By: Relevance
“…Several kinases belonging to the JNK family have been identi®ed (Gupta et al, 1996). Immunoprecipitation with anti-JNK1 antibodies and transient expression of an epitope-tagged JNK1 construct demonstrated that JNK1 is at least one of the JNKfamily members activated by Ret.…”
Section: Discussionmentioning
confidence: 99%
“…Several kinases belonging to the JNK family have been identi®ed (Gupta et al, 1996). Immunoprecipitation with anti-JNK1 antibodies and transient expression of an epitope-tagged JNK1 construct demonstrated that JNK1 is at least one of the JNKfamily members activated by Ret.…”
Section: Discussionmentioning
confidence: 99%
“…In the JNK subgroup, three genes (jnk1, jnk2 and jnk3) and ten di erent splicing variants have been described (Gupta et al, 1996;Widmann et al, 1999). JNKs are activated by two distinct MAPKKs, MKK4/SEK1 (Sanchez et al, 1994;Derijard et al, 1995), and MKK7 Yao et al, 1997;Wu et al, 1997;Tournier et al, 1997;Holland et al, 1997), in the JNK signaling unit.…”
Section: Upstream Kinases In the Jnk And P38 Modulesmentioning
confidence: 99%
“…Very recently, Gupta et al showed that both c-Jun and ATF-2 bind to and are phosphorylated by JNK, while JunB binds to but is not phosphorylated by JNK, and Elk-1 does not bind to but is phosphorylated by JNK, suggesting that the binding and phosphorylation may be distinct attributes of the interaction between JNKs and their target proteins (Gupta et al, 1996). Thus, it can be speculated that the binding of BCL-6 with MAPK may also play multiple roles besides phosphorylation.…”
Section: Phosphorylation Of Bcl-6 By Mapk In Vivo M Moriyama Et Almentioning
confidence: 99%